#### Answer

$-142$

#### Work Step by Step

$\left( a_{m}-a_{n}\right) =\left( m-n\right) d\Rightarrow a_{13}-a_{6}=\left( 13-6\right) d\Rightarrow 26-\left( -72\right) =7d=d=14;a_{6}=a_{1}+5d\Rightarrow -72=a_{1}+5\times 14\Rightarrow a_{1}=-142$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-142$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.